FINANCIAL LITERACY: DIGITAL ISLAMIC FINANCE IN COMMUNITY ECONOMIC DEVELOPMENT - Sahrani, Sahrani; Damirah, Damirah; Andika, Wahyu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
In an era marked by unprecedented global connectivity facilitated by digital platforms, the potential of integrating Islamic finance principles with advanced digital tools to elevate financial literacy and stimulate economic development becomes increasingly salient. This scholarly inquiry investigates the pivotal role of Islamic finance, underpinned by cutting-edge digital technology, in equipping the populace with indispensable financial knowledge and competencies essential for making judicious financial decisions. Moreover, it underscores the substantial contribution of this confluence towards fostering sustainable economic growth anchored in Islamic ethical frameworks. Through a comprehensive analysis of the symbiotic relationship between financial literacy, Islamic finance, and digital technology, this research delineates the opportunities, challenges, and transformative impacts on cultivating a more informed society adept at ethical and sustainable financial management. This interdisciplinary study aspires to furnish profound insights and novel perspectives in advancing an inclusive and principled economy within the contemporary digital milieu